GAME MEDIA MANAGEMENT: IMPROVING ABILITY TO KNOW THE CONCEPT OF NUMBERS THROUGH NUMBERS GAMES AT “PAUD ASMAUL HUSNA” - Nisa, Hofiyatun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Developing the ability to think in children needs to be done from an early age to provide stimulation so that children can think logically and critically and develop the ability to recognize the concept of numbers. They can use various media and methods, such as game media, to stimulate children's development. The game can produce children's thinking development because by playing indirectly, children also learn. This study aims to analyze the management of game media, which focuses on number ball media games in improving the ability to recognize numbers in early childhood. The research method used is a qualitative case study type method. This research was conducted at the Asmaul Husna PAUD institution, Sogaan, Pakuniran Probolinggo. To get a direct description, the researcher made field observations and collected data from several informants, including; school principals, bud group teachers and bloom group teachers at Asmaul Husna PAUD. The study results show that the management of the number ball game in improving the ability to recognize the concept of numbers is carried out using; analysis preparation, presentation and evaluation. Implementation obtained from the research: Children can pronounce number symbols, show number symbols, and distinguish number symbols and group number symbols.